Horticultural Crop Cultivation based on Verticulture with Utilization of Waste Materials in Jati Village, Sumberlawang Sub-district, Sragen Regency - Pinasti Dwi Utami; Hilda Putri Mauludiyah; Bramesvia Ravinka; Arisma Ria Ramadhani; Damian Paska Santyo Brahman; Dea Ramadani; Dwi Indah Lestari; Bayu Ardhy Putra; Chusnul Khotimah; Evi Gravitiani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2022)
Meeting food needs is one of the main problems for a country. Cultivation of horticultural crops with verticulture techniques is one form of activity that can be a way to meet food needs. The crop yield can be used for personal consumption and sold as a source of additional income for households. The verticulture is made from waste which are used as containers or pots and then planted with chili and mustard plants. This activity aims to improve skills, creativity, meet food needs and use empty land that can add aesthetic value. Participants consisted of 27 heads of neighborhood, the women's association for family welfare development (Pembinaan Kesejahteraan Keluarga, PKK) and Youth Organizations in Jati Village, Sumberlawang District, Sragen Regency, Sragen, with 46 participants of various ages. The activity was guided and carried out by the UNS 65 KKN team with enthusiasm and enthusiastically welcomed by the participants. The evaluation was carried out by interviewing several participants. The response showed that the activity was carried out well and the knowledge conveyed was also well received. Based on the results of these interviews, it can be seen that around 85% of participants can understand the socialization and practice of verticulture cultivation well.